Suction influence on CPT and DMT for some Brazilian tropical soils - Rocha, B. P.; Rodrigues, R. A. [UNESP]; Giacheti, H. L. [UNESP] (Taylor & Francis, 2022)
Suction plays an important role in geotechnical engineering practice since it influences the mechanical behavior of unsaturated soils. Interpretation of in situ test data at unsaturated soil sites must consider both spatial and seasonal variability, especially in strength and stiffness parameters. This paper presents and discusses CPT and DMT performed at different seasons at two sites with tropical sandy soils. CPT and DMT data were interpreted considering the influence of soil suction. Suction was estimated from water content profiles and soil water retention curves (SWRC). Failure to consider the effect of soil suction in the site investigation of unsaturated soils can lead to inappropriate soil classification as well as significant and uncon-servative overestimates of geotechnical parameters.